A family of rhodium and iridium complexes with semirigid benzylsilyl phosphines: from bidentate to tetradentate coordination modes. Issue 27 (7th April 2017) - Corona-González, María Vicky; Zamora-Moreno, Julio; Cuevas-Chávez, Cynthia A.; Rufino-Felipe, Ernesto; Mothes-Martin, Emmanuelle; Coppel, Yannick; Muñoz-Hernández, Miguel A.; Vendier, Laure; Flores-Alamo, Marcos; Grellier, Mary; Sabo-Etienne, Sylviane; Montiel-Palma, Virginia
Abstract : Rh and Ir coordination of phosphines with 1 to 3 Si–H groups. Abstract : The synthesis of a new trisbenzylsilanephosphine P( o -C6 H4 CH2 )SiMe2 H3 (1 ) is shown to proceed with high yields from P( o -tolyl)3 . Compound1 coordinates to the Rh and Ir dimers [MCl(COD)]2 (M = Rh, Ir) in a tetradentate or tridentate fashion, depending on the strict exclusion of water. The dimeric compounds [ClM(SiMe2 CH2 - o -C6 H4 )2 P( o -C6 H4 -CH2 SiMe2 H)]2, 2Rh and2Ir, feature a tetradentate coordination of the starting ligand with P and two Si atoms as well as a non-classical agostic Si–H group. The presence of adventitious water in the solvents leads to the formation of two new complexes [(μ 2 -Cl)2 M2 (SiMe2 CH2 - o -C6 H4 )2 P( o -C6 H4 -CH2 SiMe2 OSiMe2 CH2 - o -C6 H4 –)P(SiMe2 CH2 - o -C6 H4 )2 ], 3Rh and3Ir, which feature a siloxane bridge through Si–H bond breaking in2 . Reaction of [RhCl(COD)]2 with the bisbenzylsilanephosphine PhP( o -C6 H4 CH2 )SiMe2 H2 leads to the formation of compound4Rh which features also a dimeric structure with the SiPSi ligand coordinated through the two silicon atoms, one of which occupies the apical position of a square-pyramidal geometry in the solid state, while the second is disposed equatorially trans to π-donor Cl. Finally, bidentate coordination of a PSi ligand is achieved by reaction of [RhCl(COD)]2 with Ph2 P( o -C6 H4 CH2 )SiMe2 H which leads to the monometallic species [RhCl(SiMe2 CH2 - o -C6 H4 -PPh2 )2 ], 5Rh, incorporating two chelating PSi ligands and maintaining a Cl ligand.